Preferencias deportivas de la comunidad estudiantil : el caso de la Universidad de Antioquia (2013)
ABSTRACT: University of Antioquia Welfare Direction, through the Department of Sports, offers students and the university community in general, programs and activities that are educational, recreational and representative, that encourage sport, recreation and good use of leisure time. Although University Welfare Direction has a system of quality management, it does not provide sufficient information to identify the preferences of the students in these areas. Therefore, it has only a little knowledge about it, leading to possibility that the offer does not correspond to the real needs of the community. To address this problem, we developed a descriptive study,combining quantitative and qualitative methods and applying a random probability sample from the various academic units, with the aim of learning about sports preferences of the student community of the University. Among the most representative is the little sport before admission to the University and then practiced by income activities outside the University as football, cardio and gym, a low supply of institutional knowledge regarding sport and recreation and the main activities carried out by women are swimming and the gym and men, soccer and football. It also appears that the most preferred activities for students are aerobics and extreme sports.